ANALYZING THE SERVICE QUALITY OF MOVIE THEATER IN MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) CASE STUDY OF XXI MANADO TOWN SQUARE 3 - Lumentut, Pricilia Inry; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Abstract: Entertainment is a form of activity that holds the attention and interest of audience, or gives pleasure and delight. One of the entertainments part is cinema. In Indonesia, cinema’s or movie theater businesses become more increasing along the development of time. The attitude of the customer is the overall activities of the movie theater which reflect their respond about the movie theater. This research aims to analyze the service quality of Movie Theater in Manado in this case XXI Manado Town Square 3. The type of this research is a quantitative descriptive research. The Importance Performance Analysis (IPA) was used in this research. The sample of this research is 100 respondents who already experience the service quality of XXI Manado Town Square 3. The sample was taken by purposive sampling. The result of the research shows that XXI Manado Town Square 3 should maintain their good service and improve their low performance. By doing so, it is hoped that their customers will be satisfied and would be their loyal customers. Keywords: Service Quality, Importance Performance Analysis, Movie Theater, Intertainment